Nurses’ Attitudes Toward Physical Examination - Çaylı, Nazan; Nirgiz, Cansu; Kıymaç Sarı, Merve (UI Scholars Hub, 2026)
Background: This descriptive, cross-sectional study was conducted to determine the attitudes of nurses working in clinical settings toward conducting physical examinations. Methods: The sample surveyed consisted of 364 nurses currently working at 14 branches of a private hospital with facilities in seven cities, who participated voluntarily. Data was collected online via a survey created through Google Forms, applying descriptive characteristics form and the Physical Examination Attitude and Practice Scale in Nursing. The data were analyzed using the Mann–Whitney U test, Kruskal–Wallis test, Spearman’s rank-order correlation coefficient, and multiple regression analysis. Results: It was found that nurses had moderately positive attitudes toward conducting physical examinations in clinical settings, while their participation rates in in-service training related to physical examinations were low. A moderate but significant positive correlation was observed in the scores of the sub-dimension “barriers to performing physical examination,” and a very weak but significant negative correlation was found in the “benefits and usefulness of physical examination.” Conclusion: Practical training aimed at improving nurses’ knowledge and skills related to physical examination and their cultural sensitivity should be emphasized at the undergraduate level, as well as through in-service training programs.